STUDI MANAJEMEN LINGKUNGAN KEGIATAN INDUSTRI MIGAS - Tanty Juliawati; Aras Mulyadi; Mubarak ' Mubarak (Jurnal Ilmu Lingkungan, 2014)
PT. Medco E&P Indonesia - Lirik that have registered Environmental ManagementSystem (EMS) standard ISO 14001; 2004 in May of 2011. The purpose of this study are1) to analyze the environmental management system in PT. Medco E&P Indonesia -Lirik 2) to analyze whether there is a difference (gap) between EMS PT. Medco E&PIndonesia - Lirik with ISO 14001;2004, 3) to know the public perception of the industryin the surrounding of corporate activity. This research is a case study application of theISO EMS. Techniques of data collection is through direct observation of clause 4.4(implementation and operation) and clause 4.5 (examination) through document search,questionnaire and interviews with officers in the field and the community aroundthe company. Data analysis was carried out by way of valuation mismatch EMS ofPT. Medco E&P Indonesia - Lirik by EMS ISO 14001; 2004 and gap analysis. Theresults were obtained general 1) Generally PT. Medco E&P Indonesia - Lirik alreadyapplying EMS clause 4.4 (Applied and operations) and kalusul 4.5 (examination). Metsome of the non-conformance of which are in sub-clause 4.4.3 (Communication), thecommunication system in the PT. Medco E&P Indonesia - Lirik has not covered all thecompany's environmental management system and does not include all relevant parties.While clause 4.4.5 (Documentation management), found that the documents containedin the document only manual control environment and environmental procedures, andother documents are not complete. To clause 4.5.3 (a discrepancy, action, correctiveand preventive) found that PT. Medco E&P Indonesia - Lirik has not executedcorrective and preventive actions against discrepancies found in the environmentalmanagement system implemented.